Rapid response to botulinum antitoxin in hyperhidrosis patient - Kılıçaslan, Ferhat; Musabeyoğlu Kılınç, Feyza; Altunışık, Erman (Acta Medica, 2025)
Botox injections are shots that use a toxin to prevent a muscle from moving for a limited time. These shots are often used to smooth wrinkles on the face. They’re also used to treat neck spasms, sweating, overactive bladder, lazy eye and other conditions.